2003
DOI: 10.1243/095440603322407290
|View full text |Cite
|
Sign up to set email alerts
|

Laser non-conduction limited heating and prediction of surface recession velocity in relation to drilling

Abstract: Lasers nd application in modifying the characteristics of metallic surfaces in industry. In the present study, a laser non-conduction heating situation is investigated and the recession velocity of the surface is computed after considering: (a) constant temperature evaporation at the surface and (b) the steady evaporation condition. It is found that, in the initial phase of evaporation, the velocity of the liquid-vapour interface (recession velocity) predicted from constant temperature evaporation at the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This is because of the amount of energy absorbed in the surface region, which is considerably higher than at some depth below the surface where melting takes place. Comparison of recession velocity obtained from present predictions along the symmetry axis and one-dimensional analytical solution [17]. Figure 11 shows the quality in the liquid-solid mushy zone for different laser power intensities at three depths below the surface.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…This is because of the amount of energy absorbed in the surface region, which is considerably higher than at some depth below the surface where melting takes place. Comparison of recession velocity obtained from present predictions along the symmetry axis and one-dimensional analytical solution [17]. Figure 11 shows the quality in the liquid-solid mushy zone for different laser power intensities at three depths below the surface.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, increasing power intensity does not alter the magnitude of recession velocity significantly, particularly in the early heating period. Moreover, Figure 9 shows the recession velocity of the surface obtained from the previous analytical solution [17] and present predictions. It can be observed that both results are reasonably in agreement.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…They indicated that liquid ejection from the laser produced cavity should be considered for laser power intensities close to the threshold intensity for evaporation. Yilbas et al [8] investigated laser induced phase change processes in relation to drilling. However, the studies were limited to vapor front formation and vapor front expansion into its ambient was omitted.…”
Section: Introductionmentioning
confidence: 99%